State of Nature J.J. Rousseau dan Implikasinya terhadap Bentuk Ideal Negara - Lailiy Muthmainnah (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2011)
J.J. Rousseau conception about state of nature is not state of war but peace condition, abundant resources, and rooted in the pre history era. The condition changed when the savage man had been in transition to the civil society. In this situation conflict of interest appears and the State is needed to solve this problem. Rousseau proposes partisipatory democracy as ideality of the State. In the partisipatory democracy a souvereign will have important position because it will make a legislation. Because of that, all citizens must have a good political education so that their preference will be similar to general will. Keywords: state of nature, J.J. Rousseau, State, partisipatory democracy, general will.